Viceroy Abascal, Landlords and Piura bandits. Preliminary notes on social and political experience of José Sapata (a) Palomo (1814-1817) - Espinoza Claudio, César (2019)
Our research aims to trace afro-descendant resistance culture in peasant and urban people against another social force represented by landlords like Francisco Xavier Fernández de Paredes in La Chira Valley, Querecotillo, Piura. Archival judicial documentation from Piura and Lima introduced us to a rural social world with gaps and asymmetries between Indian law and social practice, while recurrence of an illegal colonial model in regions and provinces allowed us to acquaint the nature of collective protest actions, from peasant mobilizations of hatred to bloody movements that broke social peace of landlords, peasants, and cattlemen. We examined 1814-1817 events, a political situation of regional crisis. In this social time, subdelegate and mayors of San Miguel de Piura were able to see two social movements functioning but still not in an articulated manner; the first was the «savage» cimarrones and, the second was the gang of José Sapata (a) Palomo, accused of being a bandit who has traveled through cities such as Lima and Piura.